(untitled) (Comprehensive Journal of Science, 2026)
This research summarizes the role of Queen Stratonice (Stratones II) in the Hellenistic era, highlighting her royal status and political influence within the Seleucid dynasty , The first section examines her family origins and her connection to power, while the second focuses on her political marriage as a tool for strengthening alliances and reshaping the balance of power, It concludes that she was an active player on the political scene, not merely a pawn in power struggles.